Evaluation of Waft Awareness Effectiveness LED on the Substance via a Mutational-Status Method: Correlation with Dot Fractal Activity - Kim, Jeong-Lae; Kang, Eun-Young; Song, Han-Chun; Choi, Gyoo-Seok; Kang, Jeong-Jin (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Dot fractal activity (DFA) became a very useful tool in the physical sciences, with a wide range of applications to characterize different substances. The most commonly used method for calculating the DFA inside a substance is the circular arithmetic operation. This technique is often performed on images and dots. However, there is some weakness when dealing with inner circular porous surfaces in images. In this study, we present a mutational-status method for calculating the DFA of a circular porous surface based on LEDs. We used a new program, called Di-aof which is based on the LED DFA algorithm, which overcomes the limitations of existing line calculation algorithms when processing circular porous surfaces. LEDs also allow us to dealing with both global and local level evaluations at each circular porous surface vertex. Express a uneven mutational-status of the GAR-IAR, of the max-med in terms of the diffuse-tuner outward-form, and the diffuse value of the far mutational-status of the Di-aof-FA-ΨMAX-MED was 10.32±7.44 units, and the diffuse value of the convenient mutational-status of the Di-aof-CO-ΨMAX-MED was 2.73±0.39 units, and the diffuse value of the flank mutational-status of the Di-aof-FL-ΨMAX-MED was 0.97±0.32 units, and the diffuse value of the edge mutational-status of the Di-aof-VI-ΨMAX-MED was (0.16±0.09) units. Di-aof is specially designed and tested for the assessment of the circular porous surface obtained from the LED DFA algorithm based on diffuse awareness outward-form (DAOF). Nevertheless, the program can also dealing with any kind of surface in the form of a glimmer awareness rate-imbalance awareness rate (GAR-IAR). Proving usefulness by applying Di-aof to a complex study, that observes the progress of transmission and scattering in a substance. Di-aof used to develop a circular porous surface analysis of DFA calculations, and to investigate mutational-status in the distribution and spreading and scattering morphology of gels.